2014
DOI: 10.1517/14656566.2015.995625
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pharmacotherapy for opioid-induced constipation – a systematic review

Abstract: Finding a consensus definition and inclusion criteria for OIC plus a rational balance between efficacy and AEs of drugs remain future challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
0
28
0
2
Order By: Relevance
“…7 Alvimopan has similar adverse effects to those of methylnaltrexone. However, serious, but rare, adverse effects such as dehydration, bradycardia, unstable angina, and myocardial infarction are observed in alvimopan studies.…”
Section: Pharmacologic Management Laxativesmentioning
confidence: 97%
See 1 more Smart Citation
“…7 Alvimopan has similar adverse effects to those of methylnaltrexone. However, serious, but rare, adverse effects such as dehydration, bradycardia, unstable angina, and myocardial infarction are observed in alvimopan studies.…”
Section: Pharmacologic Management Laxativesmentioning
confidence: 97%
“…7 In a meta-analysis conducted to evaluate efficacy and safety of drugs in randomized controlled trials (RCTs) with adult OIC patients, methylnaltrexone was shown to be efficacious in all the objective outcome measures evaluated. 7 Of patients on methylnaltrexone, 53% to 70% had three or more rescue-free bowel movements (RFBMs) per week, and one RFBM increase over baseline compared with placebo (35% to 41%). Time to first bowel movement was shorter with methylnaltrexone.…”
Section: Pharmacologic Management Laxativesmentioning
confidence: 99%
“…It can result in a significantly reduced quality of life for patients5,8,9,14 as well as decreased adherence to the opioid regime 5,12,14…”
Section: About Opioid-induced Constipationmentioning
confidence: 99%
“…increased physical activity, fluid and dietary fibre intake) where possible 8,9,12. Laxatives should be prescribed at the point of initiating strong opioids for cancer pain15; and dual therapy with a faecal softener and a peristaltic stimulant (e.g.…”
Section: About Opioid-induced Constipationmentioning
confidence: 99%
See 1 more Smart Citation